(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
There had been significant growth in the area of renewable energy over the past recent years. Though there has been great development in sustainable energy, there is still a long way to go.There are certain inherent limits to this renewable electricity. Solar and wind electricity, for example, have an intermittent character. In comparison to the electric load, the electro-chemical reaction dynamics in the fuel cell are rather sluggish. This is incompatible with current electric applications, which demand continuous voltage and frequency. This research suggested and tested a novel power circuit to address the problem of renewable energy’s intermittent nature and poor reaction. The proposed circuit combines a variety of renewable energy sources with energy storage. The influence of intermittent nature can be considerably decreased by combining biofuels have a probabilistic proclivity towards compensating for one another. The above integration will improve the entire system’s dependability and efficiency. It may either deliver more energy to the load or absorb surplus energy from the energy sources, considerably enhancing the overall system dynamics. We provide electricity for the load using fuel cells, while solar and wind energy are employed to maintain power. We’re employing buck boost choppers and boost choppers to adjust the power to the right level. For AC loads, an inverter converts DC to AC. We use renewable energy in our project to ensure steady electricity during load. In MATLAB / Simulink, a software simulation model is created.